COVID-19: una prospettiva medica (Società e diritti, 2021)
AbstractMore than a century after the last great world pandemic, the one from Covid-19 has not been properly experienced by the Western world, that is, as a worldwide problem. Why worry if China is thousands of miles away and most Europeans have never even heard of the city Wuhan? It took a short time to rethink and deal with the most insidious and dangerous of the world’s pandemics, as a direct witness of events well describes in its various medical implications and facets, a health professional in charge of department of an important italian health reality transformed into hospital-Covid. We will not get rid of this virus soon or easily, and at best we will have to get used to it for a very long time. An appropriate worldwide vaccination campaign may succeed in solving the problem, but voluntary membership will be required without any hesitation